A Comparative Study of Manual Wagon-Top Sampling and Auto Mechanical Sampling of 200 mm Size Coal with Respect to Stopped-Belt Sampling of Thermal Coal at Indian Thermal Power Plants. Issue 2 (3rd March 2016) - Sinha, K. M. K.; Jha, G. S.; Sharma, K. K.; Singh, K. M. P.; Gouricharan, T.
ABSTRACT: The majority of the power plants in India are fed with non-coking coals where the coals are dispatched from their respective mines via wagons loaded by a rapid loading system or pay loader. The usual top size of coal is 200 mm and sampling is carried out manually from wagons. The manual method of wagon-top sampling of large size raw coal is not only difficult but also violates some of the fundamental principles of sampling. As per sampling requirements, samples are to be drawn from the full depth of the wagons, which is impossible to be done manually. Since the ash distribution in the different size fractions is not homogeneous, the results from the samples, which do not reflect the true size distribution of the lot, are likely to be biased. More importantly, sample collection by shovel from the top is a function of human discretion and not governed by the equiprobability rule. In another case, the sample has been collected by a cross-belt type auto mechanical sampler for 200 mm size coal at one of the super thermal power stations. Test analysis shows that coal collected using a cross-belt type mechanical sampler also has significant deviations from stopped-belt coal samples of 200 mm size due to size segregation. Studies carried on wagon-top sampling through specially designed experiments reveal some interesting features. The presence of bias in wagon-top sampling is apparent when compared with the "stopped-belt" sample. In this article, a comparative study between manual wagon-top sampling/auto mechanical sampling with respect to stopped-belt sampling has been conducted for coal of size 200 mm and also precision studies have been performed for wagon-top sampling/mechanical sampling for Indian thermal power plants.